Mulberry Foliage As Forage Protein Source For Sheep And Goat - Yulistiani, Dwi (Indonesian Animal Sciences Society, 2012)
Protein is one of limiting nutrient factor that determine the production level of livestock including sheep and goat. However, the price of protein feed source from oil meal or animal by-products is expensive and sometimes it is not are affordable by small scale farmers in the village. On the other hand, ruminants animal have the advantage of having rumen which able in using protein from forage to meet their protein requirement. Therefore this is important to obtain alternative feed which is cheap, affordable and have high quality and available throughout the year to increase sheep and goat productivity. Mulbery (Morus alba) plant can grow well all the year in tropical condition like Indonesia. Mulbery foliage has high protein content (> 20%), so it is potential to be used as protein foliage source in goat and sheep diet. Mulberry foliage supplementation in sheep diet could increase dry matter consumption 22.5% and followed by average daily gain 85% compared to unsuplemented diet. Key words: Mulberry foliage, protein, sheep and goat